Synthesis of reduced graphene oxide-poly(phenyleneethynylene) hybrids. A supramolecular and photophysical analyses. (28th July 2017) - Turlakov, Gleb; Arias, Eduardo; Moggio, Ivana; Jiménez-Barrera, Rosa M.; González-Morones, Pablo; Fernández, Salvador; Rodríguez, Oliverio; Ávila-Orta, Carlos; Ziolo, Ronald F.
Abstract: Functionalization of graphene oxide (GO) by esterification or amidation reactions with a series of conjugated phenyleneethynylene (PPEs) copolymers bearing different electron-donating and/or withdrawing groups was achieved by microwave irradiation in just 90 min. Copolymers as well as GO-PPE hybrids were characterized by Raman, UV–Vis, static and dynamic fluorescence spectroscopy, transmission electron microscopy, X-rays diffraction and scanning tunneling microscopy. Effective interaction of the copolymers with GO is evidenced by a strong quenching of the PPE's fluorescence quantum yield (ϕ), and by an increase of the non-radiative decay constant (Knr ); features that suggest energy transfer from PPEs copolymers to GO. HRTEM shows that the molecules of copolymers self-assemble in blocks resembling bricks or board-like shapes that can be classified as sanidic LCs materials as a general term to identify their mesomorphism. Functionalization is mainly carried out at the edges of the GO sheets, so the GO-sheets are not totally covered, even by increasing the PPE-vs-GO ratio because of the trend of the PPEs in to self-assemble in an "edge-on" conformation, meaning that the conjugated backbones are parallel to the GO surface, rather than in "face-on", where the backbones are flat-lying on the GO surface. Graphical abstract: Highlights: Functionalization of graphene oxide (GO) with phenyleneethynylene copolymers via microwave was achieved in 90 min. Energy transfer process from copolymers to GO is evidenced by a fluorescence quenching. Copolymers self-assemble in bilayers where the side chains are oriented in an opposite way in a "comb like" style.